Towards qualifications for environmental practitioners: a study of roles and competencies of entry level environmental managers - Dingela, Mcebisi Sidwell (Rhodes University, Faculty of Education, Department of Education)
The decision by the previous apartheid governments to deprive the black population of quality education and training has dealt both the people (student and workers) and the economy of this country a severe blow. That blow is demonstrated by the current lack of skills among the majority of people of this country, particularly the black workers who constitute the majority of the workforce. The post-apartheid government is making a strong attempt at redressing the past injustices in all its forms, of particular interest in this research project, the endeavours in the education and training sphere, specifically developments associated with the National Qualifications Framework. The passing into law of the South African Qualifications Act of 1995 and the formulation of the National Qualification Framework represent significant milestones towards redressing current education and training imbalances. In order to actualise the promises of these policies and laws, new qualifications will have to be developed. This research project explores training needs of environmental practitioners in three different contexts employing a combination of research methods, i.e. Case Study and a Survey. The research project sought to identify the roles and training needs of environmental management practitioners in fulfilling their job demands as well as for career advancement. The research also sought to identify through a survey training courses currently on offer in South Africa in the environmental management field. The cases revealed a range of roles and competencies required by 'entry-level' environmental managers. Of note was the observation that these roles were broader than what the traditional perspectives on environmental management might suggest, and competencies required included several social skills, in addition to various technical skills. The survey revealed a strong leaning towards technical competence among the majority of available training courses in environmental management; and that technical emphasis remained the case even among those courses that appeared to include at least one 'social' dimension. It thus seems that this emphasis on technical competence is not consistent with the job demands of the three studied environmental management practitioners. The research identified a need for an encompassing (broad) course or qualification at 'entry level' that would take into account the realities on the ground as they confront these practitioners on a daily basis. Such training will provide practitioners with the necessary competencies to function in this seemingly evolving field of environmental management. Suggestions to inform the development of an entry-level qualification or training programme are made as part of the recommendations flowing from the research findings. The suggested qualification 'framework' is based on generic areas identified among the research participants. More work is needed though in order to translate the suggestion into an accredited qualification.
Keywords: Environmental management -- South Africa; Environmental policy -- South Africa; Environmental education -- South Africa; Vocational qualifications -- South Africa; Educational equalization -- South Africa; Occupational training -- South Africa; Training needs -- South Africa; National Qualifications Framework (NQF)